2012
DOI: 10.14742/ajet.885
|View full text |Cite
|
Sign up to set email alerts
|

Impact of static graphics, animated graphics and mental imagery on a complex learning task

Abstract: The present study compared the impact of different categories of graphics used within a complex learning task. One hundred eighty five native English speaking undergraduates participated in a task that required learning 18 Chinese radicals and their English equivalent translations. A post-test only control group design compared performance differences following training between 5 groups of participants (control, concrete verbal imagery information, single static graphics, multiple gradient static graphics, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Even though self‐reported student engagement may provide some sense of the impact of teaching, it in no way captures the three types of student engagement: affective, behavioral, and cognitive 10 . Hard or direct measures of learning are less likely to be assessed and have included time spent on task, 11 performance on exams, 12 14 and final course grades 15 17 . Moreover, these studies have focused on general learning outcomes and have not identified specific types of differences in terms of learning such as recall or recognition 18 .…”
mentioning
confidence: 99%
“…Even though self‐reported student engagement may provide some sense of the impact of teaching, it in no way captures the three types of student engagement: affective, behavioral, and cognitive 10 . Hard or direct measures of learning are less likely to be assessed and have included time spent on task, 11 performance on exams, 12 14 and final course grades 15 17 . Moreover, these studies have focused on general learning outcomes and have not identified specific types of differences in terms of learning such as recall or recognition 18 .…”
mentioning
confidence: 99%
“…The strength of these static images is that, due to their stationary nature, they provide learners the opportunity to self‐regulate their processing of the material in the way they are most capable of understanding . These benefits have been explored in a number of studies where static images were found to either outperform or be equivalent to other ERs at introducing various concepts . Despite these positive results, the over use of arrows and other forms of visual shorthand to guide learners through static images has been suggested to inadvertently increase cognitive load, resulting in the creation of inaccurate mental models and student misconceptions .…”
Section: Introductionmentioning
confidence: 99%
“…Schonbron and Anderson group these factors into three categories affecting student interpretation of an ER: conceptual knowledge (student understanding of a concept), reasoning ability (student use of cognitive skills), and mode (makeup of the ER itself). Two aspects of this model, prior knowledge (representing conceptual knowledge) and spatial ability (representing reasoning ability), have been suggested to contribute to student success with both static and dynamic ERs . Previous studies have explored the importance of prior knowledge on learning outcomes when concepts were presented in both static image and dynamic animation formats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggest that learning outcomes are influenced not only by learners' characteristics and interactions with learning environments but also by the treatment of learning materials (Hede, 2002;Smith & Woody, 2000). Therefore, if instructional design is employed to treat learning materials of e-textbooks appropriately, learners will be assisted with reducing cognitive load and enhancing learning outcomes in their learning process (Lai & Newby, 2012;Sweller & Chandler, 1994). Multimedia learning materials which are perceived by both visual and audio organs (i.e., the dual-sensed method) produce a much better effect on learning outcomes than the single-sensed method (Kalyuga, 2000;van Merriënboer & Sweller, 2010).…”
Section: Introductionmentioning
confidence: 99%